Difficulties faced by third-year students in the Unimas TESL programme in studying Poetry - Jina, Lehe (Universiti Malaysia Sarawak (UNIMAS), 2004)
This study sought to identify the difficulties faced by third-year students in the UNTMAS TESL programme in studying poetry. It is also aimed at identifying the factors which contributed to the difficulties faced as well as finding out how these students managed to overcome their difficulties. It is also intended to gather recommendations and suggestions from the respondents on ways to overcome the difficulties. Data for this study was collected through the administration of open-ended questionnaire. The questionnaires were distributed to 37 third-year students in the TESL programme who make up the samples of the study. An additional instrument used in this study was the interview sessions. The findings indicated that a majority of the students encountered difficulty in studying poems with the most outstanding one being the difficulty in interpreting the meaning in the poems due to the usage of literary devices. The major factor for this difficulty is the students' low level of proficiency in the English language. In order to overcome this difficulty, a majority of the students accessed relevant sources from the Internet.